Vaccine approaches to treat urothelial cancer - Giulia Claire Giudice; Guru P. Sonpavde (Taylor & Francis Group, 2024)
Bladder cancer (BC) accounts for about 4% of all malignancies. Non-muscle-invasive BC, 75% of cases, is treated with transurethral resection and adjuvant intravesical instillation, while muscle-invasive BC warrants cisplatin-based perioperative chemotherapy. Although immune-checkpoint inhibitors, antibody drug conjugates and targeted agents have provided dramatic advances, metastatic BC remains a generally incurable disease and clinical trials continue to vigorously evaluate novel molecules. Cancer vaccines aim at activating the patient's immune system against tumor cells. Several means of delivering neoantigens have been developed, including peptides, antigen-presenting cells, virus, or nucleic acids. Various improvements are constantly being explored, such as adjuvants use and combination strategies. Nucleic acids-based vaccines are increasingly gaining attention in recent years, with promising results in other malignancies. However, despite the recent advantages, numerous obstacles persist. This review is aimed at describing the different types of cancer vaccines, their evaluations in UC patients and the more recent innovations in this field.